Regulation of autonomic nervous system by acupuncture: a heart rate variability study on physical stress - Li, Lun; Liang, Sha; Bai, Jinfeng; Zeng, Yun; Zhang, Mengzhen; Li, Zhongwen; Yan, Dingshang; Hu, Yangming; He, Liang; Liu, Yizhe; Liu, Qi; Zhang, Yingjun; et al. (Frontiers in Human Neuroscience, 2025)
IntroductionThis study aimed to investigate the effects of acupuncture and moxibustion, as well as various acupoints, on human autonomic nervous system (ANS) function and physical stress. The research further to identify effective intervention strategies for stress management and health maintenance.MethodsA Self-comparison design was conducted with healthy volunteers. Thirty-five volunteers received sequential 15-min interventions of moxibustion at ST36, acupuncture at CV12, and acupuncture at ST36, with a one-day washout period between interventions. Heart rate variability (HRV) was measured to assess autonomic function, and heart rate (HR) and the physical stress index (PSI) were measured to assess stress levels.ResultsCompared with the baseline, acupuncture at ST36 increased the high-frequency power (HF), root mean square of the successive interval difference (RMSSD), instantaneous standard deviation of the R–R interval (SD1), long-term standard deviation of the R–R intervals (SD2), total power (TP), and standard deviation of the normal–normal interval (SDNN). Acupuncture at CV12 increased RMSSD, SD1, SD2, TP and SDNN, with sustained effects for RMSSD and SD1 post-acupuncture, SD1/SD2 were increased post-acupuncture. The HRs of all three interventions decreased during the intervention, and remained sustained effects post-intervention. The PSI decreased during acupuncture and the stimulation at CV12 remained sustained effects post-acupuncture.ConclusionAcupuncture alleviates physical stress by regulating ANS activity, with distinct modulatory effects observed across different acupoints, indicating potential applications in stress management and health maintenance. Moxibustion demonstrates marked efficacy in reducing HR.Clinical trial registrationhttps://itmctr.ccebtcm.org.cn/mgt/search, ITMCTR2025001289.